The effects of ankle dorsiflexor fatigue on lower limb biomechanics during badminton forward forehand and backhand lunge - Tong, J.; Lu, Z.; Cen, X.; Chen, C.; Ugbolue, U. C.; Gu, Y. (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Local muscle fatigue may have an adverse effect on the biomechanics of the lunge movement and athletic performance. This study analyzed the biomechanical indicators of the forward lunge in badminton players before and after fatigue of the ankle dorsiflexors.